From abciximab to abelacimab. Subjective surfing upon discoveries and fiascos of biological therapies in cardiology - Róbert Gábor Kiss (Cardiologia Hungarica)
The author happened to be involved in the discovery and assessment of biological therapies, which are otherwise uncommon in the field of cardiology. Thus, he has the opportunity to draw some conclusions from his experience and, at the same time, shed light on instructive research dead ends and failures.